A review of treating viral outbreaks with self-assembled nanomaterial-like peptides: From Ebola to the Marburg virus - Alaa F. Nahhas; Thomas J. Webster (Elsevier, 2022)
Cases of the Marburg virus have started to rise and there is an urgent need to find a cure or therapy before another world-wide quarantine is introduced. There are no treatments for this virus other than giving infected people plenty of water due to excessive bleeding. Here, we report a growing strategy to use self-assembled nano peptides to attach to and inhibit viruses from replicating. Specifically, we summarize the research of others who have used this approach for Ebola, SARS-CoV-2, and other viruses and even provide our own eight octapeptides that show interference with the Marburg virus and viral RNA. These peptides self-assemble in a similar matter as the virus itself self-assembling along the viral RNA. These eight octapeptides (KLVVGDRAS, GDRASIEK, EILLAREL, ARELTLRK, FLSFCSLF, CSLFLPKL, WITWMTIW, and MTIWIPEI) were selected based on a conserved nanoparticle core sequence containing both N- and C- terminal lobes. The total atomic contact energy of these peptides as determined through computational modeling are: -110.97501, -118.57263, -99.82477, -120.60967, -17.14494, -52.11275, -14.02828, and -45.64357 kcal/mol, respectively. Collectively with results from other researchers who have designed self-assembled nano peptides to passivate other viruses, this report summarizes the strong attraction that can occur between candidate peptides and the Marburg virus. Further in vitro and in vivo studies of these peptides are needed to fully evaluate their efficacy to treat the Marburg virus, but clearly this review article demonstrates that there is a strong future for using self-assembled nano peptides to prevent and treat viral outbreaks.